Modelling and parametric analysis of cohesive behaviour of interface delamination of graphene monolayer nanocomposites. (December 2018) - Kirilova, E; Petrova, T; Becker, W; Ivanova, J
Abstract: The engineering importance of the problem of interface delamination for graphene monolayer nanocomposites is also of high level interest and it is directly connected with the optimal choice of the structure geometry and the choice of the matrix material. In this work modelling and parametric analysis of cohesive interface delamination of graphene monolayer nanocomposites are presented, using shear lag method. The external excitation of the matrix is an axial displacement, controlling the interface delamination. The statement of the considered problem is given in displacements, the interface behaviour is assumed to be a bi-linear cohesive one. Three zones along the interface are defined and for them the solutions of the system of two ordinary differential equations about the displacements of the monolayer of graphene and one for the matrix are fitted by appropriate boundary, symmetry and continuity conditions. All analytical results about the interface shear stress, the lengths of the elastic, cohesive and delaminated zones are calculated for a given structure and are illustrated in figures. The parametric analysis and the influence of the interface length, applied load and the thickness of the host layer are performed. After detailed discussion some recommendations are given.